Program Tahfidz Al-Qur’an dalam Meningkatkan Sikap Religius Siswa SD Islam Wali Songo - Wijayanti, Intan (IBTIDA', 2024)
Many elementary schools in Indonesia, optimize Islamic nuanced learning, namely by implementing the Tahfidz Al-Qur'an program, to develop religious attitudes in students, one of which is SD Islam Wali Songo. Researchers use qualitative research methods and research results are narrative descriptive. Data collection techniques in the form of documentation, observation and interviews. Data analysis in this research is nonstatistical with stages: reduction; display and conclusions. The results of this research are: first, implementation of the Tahfidz program at SD Islam Wali Songo through the planning stages by setting goals; organizing, by appointing the person in charge of the program and preparing an activity schedule; implementation and evaluation consisting of daily, monthly and annual evaluations. Second, the Tahfidz Qur'an program at SD Islam Wali Songo affects students' religious attitudes, namely the growth of love for Allah SWT. and the Qur'an, and having better morals. Third, the supporting factors for the implementation of the Tahfidz program at SD Islam Wali Songo are: all tahfidz teachers are memorizers of the Qur'an; adequate infrastructure; and 3) affordable cost. While the inhibiting factors of the tahfidz program include: some students are still often late due to the schedule of tahfidz activities earlier; the number of tahfidz teachers is limited; and feelings of laziness and hopeless.